Thermo-kinetic study to elucidate the bioenergy potential of Maple Leaf Waste (MLW) by pyrolysis, TGA and kinetic modelling. (1st June 2021) - Ahmad, Muhammad Sajjad; Klemeš, Jiří Jaromír; Alhumade, Hesham; Elkamel, Ali; Mahmood, Abid; Shen, Boxiong; Ibrahim, Muhammad; Mukhtar, Ahmad; Saqib, Sidra; Asif, Saira; Bokhari, Awais
Highlights: The feasibility of Maple Leaf Waste (MLW) for biofuel synthesis is reported. Different Kinetic models were developed and compared with each other. Activation energy through all models were ranging from 75 to 91 kJ mol −1 . All thermodynamic results reflect the remarkable bioenergy potential of the MLW. Abstract: The present study aims to evaluate the feasibility of Maple Leaf Waste (MLW) for the first time to produce biofuel-bioenergy and chemicals. It is meaningful to understand the thermochemical conversion and degradation pattern of the MLW to evaluate its biofuel-bioenergy potential. Different degradation stages and zones based on temperature and mass loss were identified to understand the pyrolytic behaviour in depth. Four different heating rates were used to conduct kinetic and thermodynamic analysis. The pyrolysis temperature was concluded ranged from 200 °C to 430 °C at all heating rates to obtain maximum bioenergy products. The kinetic parameters of pyrolysis were obtained by analysing through iso-conversional models of Kissinger-Akahira-Sunose (KAS), Friedman and Flynn–Wall–Ozawa (FWO). The average values of activation energies (75–91 kJ mol −1 ), high heating values (16.32 MJ kg −1 ), Gibb's free energies (261–269 kJ mol −1 ) and change in enthalpy (68–85 kJ mol −1 ) have shown the significant potential for bioenergy production and suitability of co-pyrolysis with other waste and biomass feedstock.